Financial Literacy and Individual Investors’ Stock Market Participation in Nepal - Lamichhane, Pitambar (Tribhuvan University Journal, 2022)
This study aims to examine the impact of financial literacy on individual investors’ stock market participation (SMP). The data were collected through a survey-structured questionnaire. This paper has applied descriptive as well as causal research design to examine the effect of financial literacy on individual investors’ stock market participation (SMP) in Nepal. Investors’ SMP is a dependent variable and financial literacy-related variables; financial knowledge, behavior, and attitude are considered as explanatory variables. The results of this paper show that investors who are participating in the Nepalese stock market have a high level of basic financial knowledge on taxes, time value of money, money illusion, and inflation. In addition, descriptive results reveal that investors have advanced financial knowledge with positive financial behavior and attitudes which implies a higher level of financial literacy of stock investors. Moreover, correlation results indicate a positive association of financial literacy with individual investors’ SMP. Finally, the regression results of this study conclude financial literacy variables (financial knowledge, behavior, and attitude) all have a positive and significant impact on investors’ stock market participation in Nepal. The Nepalese government, the policy makers, and the regulatory bodies of the stock market should make effective and sound policies and programs to increase individual investors’ financial knowledge, positive behavior, and attitude which lead to attracting more individual investors for stock market participation in Nepal.